A man called Ove : a novel - Backman, Fredrik, 1981-; Koch, Henning, 1962- (New York : Atria Books, 2014)
At first sight, Ove is almost certainly the grumpiest man you will ever meet. Ove's well-ordered, solitary world gets a shake-up one morning when new neighbors accidently flatten Ove's mailbox. This is a tale of unkempt cats and unlikely friendships.
Translated from the Swedish.
Translation of: Man som heter Ove.
"First published in Great Britain in 2014 by Hodder & Stoughton"--Title page verso.
Keywords: Older men -- Fiction; Neighbors -- Fiction; Neighborhoods -- Fiction